Sheet-like cushioning foam material for athletic running shoes and method of making same

CN122917518APending Publication Date: 2026-10-16诚达责任有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611114984.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-27
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0003]针对现有发泡材料密度与回弹性能难以兼顾、且支撑与缓震功能无法一体化的技术缺陷,本发明提供一种用于运动跑鞋的片状缓震发泡材料及其制备方法;本发明通过引入经反应性表面改性的纳米增强相构建泡孔壁协同承载网络,并结合非平衡态超临界流体发泡工艺构建梯度密度泡孔结构,实现材料密度降低的同时,提高能量回弹效率与分级缓震支撑能力

Benefits of technology

本发明通过引入与热塑性弹性体基体形成化学键合的表面改性纳米增强相,结合连续渐变的梯度密度泡孔结构,使片状缓震发泡材料在具备较低表观密度的同时,有效提升了能量回弹率和分级缓震支撑能力。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present application relates to the technical field of high polymer foaming material, in particular to a sheet-shaped cushioning foaming material for sports running shoes and a preparation method thereof; the foaming material comprises a thermoplastic elastomer matrix and a surface-modified nano-reinforced phase chemically bonded to the thermoplastic elastomer matrix, and the preparation process comprises nano-phase modification, master batch preparation, precursor forming, non-equilibrium supercritical fluid impregnation, stepwise pressure relief foaming and cooling and setting, etc.; the core of the foaming material is to introduce the surface-modified nano-reinforced phase to construct a bubble wall bearing network, and to use pre-desorption and stepwise pressure relief process to construct a gradient structure with high-density support on the outside and low-density cushioning on the inside; the foaming material overcomes the defect that light weight and high resilience are difficult to be considered simultaneously; the apparent density of the foaming material is 0.15-0.25 g / cm3, the energy resilience rate is up to 68.5%, and the thickness retention rate after 100,000 times of dynamic compression is 96.8%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of polymer foam materials technology, specifically to sheet-like cushioning foam materials for sports running shoes and their preparation methods. Background Technology

[0002] In the field of professional sports shoe materials, the lightweight and cushioning rebound performance of midsole materials are key indicators that determine the overall performance of running shoes; traditional polymer foam materials usually achieve lightweighting by increasing the foaming ratio. However, increasing the foaming ratio inevitably leads to thinner cell walls and a smaller cross-sectional area for material load-bearing, resulting in decreased compressive strength and susceptibility to permanent compression deformation. Its energy return rate is usually below 50%. This mutual constraint between lightweight and high resilience makes it difficult for existing foamed materials to meet the high technical requirements of professional sports for extremely low apparent density and high energy return rate. In addition, existing foam materials mostly exhibit a uniform cell structure. When subjected to impact, the uniform structure cannot achieve a graded stress response. As a result, while the material provides excellent cushioning deformation capacity, it often lacks sufficient stiffness, causing excessive foot roll and increasing the risk of sports injuries. Summary of the Invention

[0003] To address the technical shortcomings of existing foam materials, such as the difficulty in simultaneously achieving both density and rebound performance, and the inability to integrate support and cushioning functions, this invention provides a sheet-like cushioning foam material for running shoes and its preparation method. This invention introduces a reactive, surface-modified nano-reinforcing phase to construct a synergistic load-bearing network within the cell walls, and combines this with a non-equilibrium supercritical fluid foaming process to create a gradient-density cell structure. This achieves a reduction in material density while simultaneously improving energy rebound efficiency and graded cushioning support capabilities. The specific technical solution is as follows: A sheet-like cushioning foam material for athletic running shoes includes a thermoplastic elastomer matrix and a surface-modified nano-reinforcing phase dispersed in the thermoplastic elastomer matrix; the surface-modified nano-reinforcing phase forms a chemical bond with the thermoplastic elastomer matrix. The sheet-like shock-absorbing foam material has a continuously varying gradient density cell structure along its thickness direction. The gradient density cell structure includes an outer high-density layer, an inner low-density layer, and a gradient transition layer between the outer high-density layer and the inner low-density layer. The pore size of the outer high-density layer is 50-150 μm, and the pore size of the inner low-density layer is 200-500 μm. The apparent density of the sheet-like shock-absorbing foam material is 0.15-0.25 g / cm³.

[0004] Preferably, the thermoplastic elastomer matrix is ​​selected from one or more of ethylene-vinyl acetate copolymer, thermoplastic polyurethane elastomer, and polyether block amide copolymer.

[0005] Preferably, the surface-modified nano-reinforcing phase is selected from one or more of graphene nanosheets and multi-walled carbon nanotubes with carboxyl groups and / or hydroxyl groups on the surface and grafted with isocyanate or silane coupling agent; the mass fraction of the surface-modified nano-reinforcing phase in the thermoplastic elastomer matrix is ​​0.1wt%-2.0wt%.

[0006] Preferably, the outer high-density layer, the gradient transition layer, and the inner low-density layer are continuous, and the pore size and pore density are distributed in a continuous gradient along the thickness direction.

[0007] Preferably, a method for preparing a sheet-like cushioning foam material for athletic running shoes as described in any of the preceding claims includes the following steps: S1. Modification of nano-reinforcing phase: The nano-reinforcing phase is acidified to introduce carboxyl and / or hydroxyl active groups, and then grafted with isocyanate or silane coupling agent to obtain a surface-modified nano-reinforcing phase; S2. Masterbatch preparation: The surface-modified nano-reinforcing phase is melt-blended with a thermoplastic elastomer matrix to obtain a nanocomposite masterbatch; S3. Precursor sheet forming: The nanocomposite masterbatch is mixed with the thermoplastic elastomer matrix and formed to obtain a solid precursor sheet; S4. Non-equilibrium supercritical fluid impregnation: The solid precursor sheet is placed in an autoclave, supercritical fluid is introduced and pressure is maintained at impregnation temperature and pressure until saturation, and then controlled pre-desorption is performed, that is, the pressure is reduced to 60%-80% of the impregnation pressure at a depressurization rate of 0.1-1.0 MPa / min and maintained at pressure for 10-30 min; S5. Stepped depressurization foaming: Apply a temperature gradient to the solid precursor sheet that has undergone the controlled pre-desorption treatment. Specifically, the inner wall of the autoclave and the gas medium are cooled by opening the autoclave cooling jacket. A temperature gradient with a surface temperature lower than the core temperature is established in the thickness direction of the solid precursor sheet, and 2-3 pressure platforms are used for stepped depressurization. S6. Cooling and Shaping: The foamed sheet is rapidly cooled to below the glass transition temperature or crystallization temperature of the thermoplastic elastomer matrix to obtain the sheet-like cushioning foam material for sports running shoes.

[0008] Preferably, the acidification treatment in S1 uses a mixture of concentrated nitric acid and concentrated sulfuric acid, with a volume ratio of 1:3; the acidification treatment is carried out by ultrasonic dispersion; the grafting reaction is carried out in anhydrous N,N-dimethylformamide, the grafting reagent is 4,4-diphenylmethane diisocyanate, the reaction temperature is 60°C, the reaction time is 12 h, and the reaction is carried out under nitrogen protection.

[0009] Preferably, the melt blending in S2 is carried out using a twin-screw extruder, and the melt blending temperature is 165-195℃.

[0010] Preferably, the thickness of the solid precursor sheet in S3 is 3 mm; the supercritical fluid in S4 is supercritical carbon dioxide, the impregnation temperature is 145°C, the impregnation pressure is 20 MPa, and the holding time is 2 h; the controlled pre-desorption includes reducing the pressure to 15 MPa at a depressurization rate of 0.1-1.0 MPa / min and holding it for 15 min.

[0011] Preferably, the stepped pressure relief in S5 includes: a first stage reducing the pressure from 15MPa to 8MPa at a rate of 15MPa / s; a second stage holding the pressure at 8MPa for 5s; and a third stage reducing the pressure to 0.1MPa at a rate of 10MPa / s. The temperature gradient is achieved by opening the cooling jacket to establish a temperature field on the surface of the sheet that is lower than that in the core. In S6, a 20°C cold water bath is used for quenching and cooling.

[0012] The beneficial effects of this invention are as follows: This invention introduces a surface-modified nano-reinforcing phase that forms a chemical bond with a thermoplastic elastomer matrix, combined with a continuously gradient density cell structure, enabling the sheet-like shock-absorbing foam material to effectively improve energy rebound rate and graded shock-absorbing support capability while having a low apparent density. Detailed Implementation

[0013] The technical solutions in the embodiments of the present invention will be clearly and completely described below; the described embodiments are some embodiments of the present invention, but not all embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are within the scope of protection of the present invention. Example 1: This example provides a sheet-like cushioning foam material for sports running shoes. The specific preparation steps are as follows: In this example, the average outer diameter of the multi-walled carbon nanotubes used is 15nm and the average length is 20μm; the hardness of the polyester thermoplastic polyurethane elastomer particles is 90A. S1. Nano-reinforced phase modification and masterbatch preparation: 10g of multi-walled carbon nanotubes were ultrasonically acidified with a mixture of concentrated nitric acid and concentrated sulfuric acid in a volume ratio of 1:3 to introduce carboxyl and hydroxyl groups. After washing to neutrality, the nanotubes were dried. The dried nanotubes were dispersed in 500mL of anhydrous N,N-dimethylformamide, and 20g of 4,4-diphenylmethane diisocyanate and 0.20g of dibutyltin dilaurate were added. The mixture was reacted at 60℃ under nitrogen protection for 12h. After the reaction, the nanotubes were washed and dried to obtain multi-walled carbon nanotubes with surface isocyanate groups modified. The isocyanate groups on the surface of the multi-walled carbon nanotubes modified with surface isocyanate groups can react with the active groups in the subsequent TPU matrix, thereby improving the dispersion uniformity of the nano-reinforcing phase in the matrix and the interfacial bonding strength. Surface isocyanate-modified multi-walled carbon nanotubes were melt-blended with polyester-type TPU particles at a mass ratio of 15:85 using a twin-screw extruder. The temperatures of each zone of the twin-screw extruder were set sequentially to 175℃, 180℃, 185℃, 190℃, and 195℃ to obtain a nanocomposite masterbatch. The mass fraction of multi-walled carbon nanotubes in the nanocomposite masterbatch was 15%. The obtained nanocomposite masterbatch was used to pre-disperde the nano-reinforcing phase uniformly in TPU, reduce agglomeration during subsequent sheet forming, and provide a reinforcing skeleton for the formation of stable cell walls. S2. Precursor sheet forming: Nanocomposite masterbatch and pure TPU particles were dry-mixed uniformly at a mass ratio of 1:14, and hot-pressed at 195℃ using a flat vulcanizing machine to obtain a solid precursor sheet with a thickness of 3mm. The solid precursor sheet is used to provide a uniform adsorption matrix for subsequent supercritical fluid impregnation and to ensure the stability of the gas diffusion path in the thickness direction during the subsequent pre-desorption process, thereby facilitating the formation of a controllable gas concentration gradient. S3. Non-equilibrium supercritical fluid impregnation: Solid precursor sheets are placed in an autoclave, and supercritical carbon dioxide is introduced. The pressure is maintained at 145℃ and 20MPa for 2 hours to saturate the carbon dioxide in the sheet. The pressure is then slowly reduced to 15MPa and maintained for 15 minutes to form a gas concentration gradient in the thickness direction of the sheet. The gas concentration gradient gives the surface layer and the core of the sheet different driving forces for nucleation and cell growth during subsequent depressurization, which is a prerequisite for obtaining a high-density outer layer and a low-density inner layer. S4. Stepped pressure relief and non-isothermal foaming: Open the cooling jacket and circulate 5℃ cooling water for 2-5 minutes to establish a temperature field on the sheet surface that is lower than that in the core. Use a three-stage stepped pressure relief method: the first stage reduces the pressure from 15MPa to 8MPa at a rate of 15MPa / s; the second stage holds the pressure at 8MPa for 5 seconds; and the third stage reduces the pressure to 0.1MPa at a rate of 10MPa / s. The sheet material has a high-density microporous surface and a low-density macroporous core, forming a gradient density cell structure with a continuous gradient along the thickness direction. The high-density microporous surface mainly provides support and inhibits local collapse, while the low-density macroporous core mainly acts as a buffer and absorbs energy. The gradual transition between the two reduces interfacial stress concentration. S5. Cooling and Shaping: The foamed sheet is placed in a 20°C cold water bath for quenching and cooling to obtain sheet-like cushioning foam material for sports running shoes; quenching and cooling is used to quickly freeze the formed gradient cell structure, reduce the continued enlargement or collapse of cells, thereby stabilizing the final apparent density and rebound performance. The performance test results are as follows: the apparent density is 0.18 g / cm³, the energy rebound rate tested according to ASTM D2632 standard is 68.5%, the thickness permanent deformation rate after 100,000 dynamic compressions under SATRA™ 156 standard is 3.2%, and the thickness retention rate is 96.8%. The cross-sectional morphology of the foamed material was observed and characterized by scanning electron microscopy, and the pore size was statistically analyzed. The results show that the average pore size of the outer high-density layer is 65 μm, and the average pore size of the inner low-density layer is 280 μm.

[0014] Example 2: This example provides a sheet-like cushioning foam material for sports running shoes. The specific steps are as follows: In this example, the thickness of the graphene nanosheets used is 1-5nm and the sheet diameter is 5-10μm; the thermoplastic polyurethane elastomer and polyether block amide used are both commercially available conventional products. S1. After acidification treatment of 8g of graphene nanosheets, carboxyl and hydroxyl groups were introduced, and the nanosheets were dispersed in 400mL of anhydrous N,N-dimethylformamide. 12g of 4,4-diphenylmethane diisocyanate and 0.12g of dibutyltin dilaurate were added, and the grafting reaction was carried out at 60℃ under nitrogen protection for 12h to obtain graphene nanosheets with surface isocyanate groups modified. Graphene nanosheets with surface isocyanate groups modified are beneficial to enhancing the interfacial compatibility between them and the TPU / PEBAX blend matrix, and improving the synergistic effect of rigidity and toughness of the subsequent cell walls. The graphene nanosheets were melt-blended with a TPU and PEBAX blend matrix using a twin-screw extruder, with a TPU to PEBAX mass ratio of 7:3 and a melt-blending temperature of 180℃ to 190℃, specifically 180℃, 185℃, 190℃, and 190℃ respectively, to obtain a nanocomposite masterbatch with a graphene nanosheet mass fraction of 0.8wt%. The obtained nanocomposite masterbatch was used to pre-disperse the graphene nanosheets in the blend matrix to reduce the stacking and local enrichment of the sheets when added directly. S2. The nanocomposite masterbatch is mixed with pure TPU and PEBAX blend at a mass ratio of 1:3 and then formed using a flat vulcanizing machine to obtain a solid precursor sheet with a thickness of 3mm. The solid precursor sheet is used to ensure that there is a stable mass transfer path and uniform thickness conditions inside the sheet during subsequent supercritical carbon dioxide impregnation, so as to facilitate the establishment of gas concentration differences in the thickness direction. S3. Place the precursor sheet in an autoclave, introduce supercritical carbon dioxide, and maintain the pressure at 145℃ and 18MPa for 2 hours. Then reduce the pressure to 14MPa and maintain it for 10 minutes. This pre-desorption step allows the surface of the sheet to release some gas while the core retains more gas, thus providing conditions for the subsequent formation of a gradient pore structure with a dense outer layer and a sparse inner layer. S4. Open the cooling jacket to establish a temperature gradient, and use a two-stage stepped depressurization to reduce the pressure from 14MPa to 7MPa and hold it for 5s, and then reduce it to 0.1MPa to form a gradient density bubble structure; the high-density outer layer can improve the compressive strength, and the low-density inner layer can enhance the impact energy absorption capacity. S5. Quench and cool the foamed sheet to set its shape; quenching and setting can inhibit the continued growth and co-occurrence of cells and fix the existing gradient structure. The performance test results are as follows: apparent density is 0.16 g / cm³, energy rebound rate is 66.2%, thickness permanent deformation rate is 4.0%, and thickness retention rate is 95.9%. The cross-sectional morphology of the foamed material was observed and characterized by scanning electron microscopy, and the pore size was counted. The results showed that the pore size of the outer high-density layer was 60-90 μm, and the pore size of the inner low-density layer was 250-400 μm.

[0015] Example 3: This example provides a sheet-like cushioning foam material for running shoes. The specific steps are as follows: In this example, the multi-walled carbon nanotubes used have an outer diameter of 10-20 nm and a length of 10-30 μm; the vinyl acetate content of the ethylene-vinyl acetate copolymer used is 26%. S1. After acidifying 10g of multi-walled carbon nanotubes with mixed acid, they were grafted and modified with a silane coupling agent. Specifically, the acidified multi-walled carbon nanotubes were dispersed in a 95% (v / v) ethanol aqueous solution, 1.0g of silane coupling agent KH550 was added, and the pH of the system was adjusted to 4.5 with glacial acetic acid. The reaction was carried out at 75℃ for 4h, filtered, washed, and dried to obtain surface-modified multi-walled carbon nanotubes. The silane coupling agent forms a graft layer on the surface of the multi-walled carbon nanotubes, which can improve the interfacial wettability and dispersion stability with the EVA / TPU blend matrix. The mixture was melt-blended with an EVA and TPU blend matrix, wherein the mass ratio of EVA to TPU was 6:4. The temperatures of each zone of the twin-screw extruder were set sequentially to 165℃, 170℃, 175℃ and 180℃ to obtain a nanocomposite masterbatch with a multi-walled carbon nanotube mass fraction of 0.5wt%. The obtained nanocomposite masterbatch was used to first establish a uniform dispersion of the nano-reinforcing phase to avoid local agglomeration of the reinforcing phase in the subsequent sheet, which would affect the foaming uniformity. S2. The nanocomposite masterbatch is mixed with pure EVA and TPU blend at a mass ratio of 1:4 and then hot-pressed to obtain a solid precursor sheet with a thickness of 3 mm. The solid precursor sheet provides a stable shape basis for subsequent supercritical fluid impregnation and pre-desorption, and helps to establish a repeatable gas concentration gradient in the thickness direction. S3. Place the precursor sheet in an autoclave, introduce supercritical carbon dioxide, and maintain the pressure at 150℃ and 20MPa for 2 hours. Then slowly reduce the pressure to 15MPa and maintain it for 15 minutes. This step allows the core to retain a higher concentration of carbon dioxide than the surface layer, while the surface layer has a relatively lower gas content due to pre-desorption, creating conditions for subsequent differentiated foaming. S4. Open the cooling jacket to establish a temperature gradient and adopt a three-stage stepped pressure relief to form a relatively dense microporous layer on the outside and a relatively loose macroporous layer on the inside. The relatively dense microporous layer mainly improves the outer support and fatigue resistance of the sheet, while the relatively loose macroporous layer mainly provides shock absorption and energy absorption space. S5. Quench and cool the foamed sheet to set its shape; quenching and cooling are used to quickly fix the formed cell size and interlayer gradient state, and reduce structural shrinkage. The performance test results are as follows: apparent density is 0.22 g / cm³, energy rebound rate is 62.4%, thickness permanent deformation rate is 5.6%, and thickness retention rate is 94.2%. The cross-sectional morphology of the foamed material was observed and characterized by scanning electron microscopy, and the pore size was statistically analyzed. The results showed that the pore size of the outer high-density layer was 80-120 μm, and the pore size of the inner low-density layer was 300-450 μm.

[0016] Example 4: This example provides a sheet-like cushioning foam material for sports running shoes, and the specific steps are as follows; S1. Take 10g of graphene nanosheets and treat them with ultrasonic acidification using a mixture of concentrated nitric acid and concentrated sulfuric acid in a volume ratio of 1:3 to introduce carboxyl and hydroxyl groups. Wash until neutral and then dry. Disperse the dried graphene nanosheets in 500mL of anhydrous N,N-dimethylformamide, add 20g of 4,4-diphenylmethane diisocyanate and 0.20g of dibutyltin dilaurate, and react at 60℃ under nitrogen protection for 12h. Wash and dry to obtain graphene nanosheets with surface isocyanate groups modified. The graphene nanosheets were melt-blended with a TPU matrix at a mass ratio of 2:98 using a twin-screw extruder at a melt-blending temperature of 175-195℃ to obtain a nanocomposite masterbatch with a graphene nanosheet mass fraction of 2.0 wt%. S2. The nanocomposite masterbatch and pure TPU particles are mixed at a mass ratio of 1:1 and then hot-pressed to obtain a solid precursor sheet with a thickness of 3mm. S3. Place the precursor sheet in an autoclave, introduce supercritical carbon dioxide, maintain the pressure at 140℃ and 20MPa for 2 hours, then slowly reduce the pressure to 15MPa and maintain it for 15 minutes. S4. Open the cooling jacket to establish a temperature gradient, and use a three-stage stepped pressure relief to form a continuous gradient cell structure in the thickness direction of the sheet. S5. Quench, cool and set the foamed sheet; The performance test results are as follows: apparent density is 0.25 g / cm³, energy rebound rate is 60.8%, thickness permanent deformation rate is 6.1%, and thickness retention rate is 93.8%. The cross-sectional morphology of the foamed material was observed and characterized by scanning electron microscopy, and the pore size was statistically analyzed. The results showed that the pore size of the outer high-density layer was 90-130 μm, and the pore size of the inner low-density layer was 350-480 μm.

[0017] Comparative Example 1: The difference between this comparative example and Example 1 is that the isocyanate grafting modification on the surface of the multi-walled carbon nanotubes in step S1 is omitted, and unmodified multi-walled carbon nanotubes are used directly instead. Other operation steps and process parameters are exactly the same as in Example 1. The performance test results are as follows: apparent density is 0.19 g / cm³, energy rebound rate is 54.6%, thickness permanent deformation rate is 8.9%, and thickness retention rate is 88.1%.

[0018] Comparative Example 2: The difference between this comparative example and Example 1 is that the controlled pre-desorption treatment in step S3 is omitted, while the other operating steps and process parameters are exactly the same as in Example 1. The performance test results are as follows: apparent density is 0.20 g / cm³, energy rebound rate is 56.8%, thickness permanent deformation rate is 8.1%, and thickness retention rate is 89.4%.

[0019] Comparative Example 3: The difference between this comparative example and Example 1 is that the three-stage stepped depressurization in step S4 is replaced with a one-time depressurization to 0.1MPa, while the other operating steps and process parameters are exactly the same as in Example 1; The performance test results are as follows: apparent density is 0.19 g / cm³, energy rebound rate is 52.3%, thickness permanent deformation rate is 9.5%, and thickness retention rate is 87.2%.

[0020] Comparative Example 4: The difference between this comparative example and Example 1 is that the temperature gradient establishment in step S4 is cancelled, the temperature field in the thickness direction of the sheet remains consistent during the foaming process, and the other operation steps and process parameters are exactly the same as in Example 1. The performance test results are as follows: apparent density is 0.18 g / cm³, energy rebound rate is 55.1%, thickness permanent deformation rate is 7.8%, and thickness retention rate is 90.0%.

[0021] Comparative Example 5: The difference between this comparative example and Example 1 is that the mass fraction of multi-walled carbon nanotubes in the final sheet is increased from 1.0 wt% to 2.5 wt%. Specifically, the dry mixing mass ratio of nanocomposite masterbatch and pure TPU particles in step S2 is adjusted from 1:14 to 1:5. Other operating steps and process parameters are exactly the same as in Example 1. The performance test results are as follows: apparent density is 0.21 g / cm³, energy rebound rate is 58.2%, thickness permanent deformation rate is 7.2%, and thickness retention rate is 91.3%.

[0022] Performance Tests and Data Sheets: Apparent density was obtained by converting mass to volume; energy rebound rate was tested according to ASTM D2632 standard; thickness permanent deformation rate and thickness retention rate were determined after 100,000 dynamic compression tests according to SATRA™ 156 standard; specific test results are shown in Table 1.

[0023] Table 1. Performance test results of each embodiment and comparative example. As can be seen from the comparison of the test results of Example 1 and Comparative Example 1 in Table 1, the omission of isocyanate grafting modification on the surface of multi-walled carbon nanotubes leads to a decrease in energy rebound rate and an increase in thickness permanent deformation rate. The unmodified multi-walled carbon nanotubes and TPU matrix are mainly bonded by physical action, and the interfacial bonding strength is weak. It is difficult to form a stable synergistic bearing network in the cell wall during the foaming process. The cell wall is more prone to slippage and local instability during compression and rebound, thus reducing the rebound ability. As can be seen from the comparison of the test results of Example 1 and Comparative Example 2 in Table 1, the omission of controlled pre-desorption treatment leads to a decrease in energy rebound rate and an increase in thickness permanent deformation rate; a stable gas concentration gradient is not formed in the thickness direction of the sheet, the nucleation driving force is unevenly distributed during foaming, the layered control effect of cell size and pore density is weakened, the structural difference between the outer support layer and the inner damping layer becomes smaller, and the material's graded response capability to impact load decreases; As can be seen from the comparison of the test results of Example 1 and Comparative Example 3 in Table 1, replacing the step-by-step pressure relief with a one-time pressure relief resulted in a significant decrease in the energy rebound rate. When the pressure is released rapidly in one go, the carbon dioxide precipitation rate in the matrix is ​​too fast, and the cell growth and shaping process is not easy to be controlled synchronously. Cell merging and cell wall thinning are likely to occur, the uniformity of cell structure decreases, and the elastic recovery ability of the material is weakened. As can be seen from the comparison of the test results of Example 1 and Comparative Example 4 in Table 1, after the temperature gradient is removed, the energy rebound rate decreases and the thickness retention rate decreases. When there is no temperature difference in the thickness direction, the difference in melt viscosity between the surface layer and the core is weakened, the cell growth rate tends to be consistent, it is difficult to form an outer high-density layer and an inner low-density layer, the gradient structure is not obvious, resulting in insufficient division of labor between support and shock absorption when the material is under pressure. As can be seen from the comparison of the test results of Example 1 and Comparative Example 5 in Table 1, increasing the mass fraction of multi-walled carbon nanotubes to 2.5 wt% leads to a decrease in energy rebound rate and an increase in thickness permanent deformation rate. When the content of nano-reinforcing phase is too high, the dispersion difficulty increases, local agglomeration weakens the continuity of the cell wall, and at the same time increases the melt flow resistance, affecting the diffusion of supercritical fluid in the matrix and the uniform growth of cells. The material is more prone to local stress concentration and structural damage under cyclic compression.

[0024] The above are merely specific embodiments of the present invention and are not intended to limit the present invention in any other way. Any person skilled in the art may make changes or modifications to the above-disclosed technical content to create equivalent embodiments for application in other fields. However, any conventional modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the technical solution of the present invention shall still fall within the protection scope of the technical solution of the present invention.

Claims

1. A sheet-like cushioning foam material for sports running shoes, characterized in that, The product comprises a thermoplastic elastomer matrix and a surface-modified nano-reinforcing phase dispersed in the thermoplastic elastomer matrix; the surface-modified nano-reinforcing phase forms a chemical bond with the thermoplastic elastomer matrix; The sheet-like shock-absorbing foam material has a continuously varying gradient density cell structure along its thickness direction. The gradient density cell structure includes an outer high-density layer, an inner low-density layer, and a gradient transition layer between the outer high-density layer and the inner low-density layer. The pore size of the outer high-density layer is 50-150 μm, and the pore size of the inner low-density layer is 200-500 μm. The apparent density of the sheet-like shock-absorbing foam material is 0.15-0.25 g / cm³.

2. The sheet-like cushioning foam material for sports running shoes according to claim 1, characterized in that, The thermoplastic elastomer matrix is ​​selected from one or more of ethylene-vinyl acetate copolymer, thermoplastic polyurethane elastomer, and polyether block amide copolymer.

3. The sheet-like cushioning foam material for sports running shoes according to claim 1 or 2, characterized in that, The surface-modified nano-reinforcing phase is selected from one or more of graphene nanosheets and multi-walled carbon nanotubes with carboxyl groups and / or hydroxyl groups on the surface and grafted with isocyanate or silane coupling agents; the mass fraction of the surface-modified nano-reinforcing phase in the thermoplastic elastomer matrix is ​​0.1wt%-2.0wt%.

4. The sheet-like cushioning foam material for athletic running shoes according to any one of claims 1 to 3, characterized in that, The outer high-density layer, the gradient transition layer, and the inner low-density layer remain continuous, and the pore size and pore density are distributed in a continuous gradient along the thickness direction.

5. A method for preparing a sheet-like shock-absorbing foam material for sports running shoes as described in any one of claims 1 to 4, characterized in that, Includes the following steps: S1. Modification of nano-reinforcing phase: The nano-reinforcing phase is acidified to introduce carboxyl and / or hydroxyl active groups, and then grafted with isocyanate or silane coupling agent to obtain a surface-modified nano-reinforcing phase; S2. Masterbatch preparation: The surface-modified nano-reinforcing phase is melt-blended with a thermoplastic elastomer matrix to obtain a nanocomposite masterbatch; S3. Precursor sheet forming: The nanocomposite masterbatch is mixed with the thermoplastic elastomer matrix and formed to obtain a solid precursor sheet; S4. Non-equilibrium supercritical fluid impregnation: The solid precursor sheet is placed in an autoclave, supercritical fluid is introduced and pressure is maintained at impregnation temperature and pressure until saturation, and then controlled pre-desorption is performed, that is, the pressure is reduced to 60%-80% of the impregnation pressure at a depressurization rate of 0.1-1.0 MPa / min and maintained at pressure for 10-30 min; S5. Stepped depressurization foaming: Apply a temperature gradient to the solid precursor sheet that has undergone the controlled pre-desorption treatment. Specifically, the inner wall of the autoclave and the gas medium are cooled by opening the autoclave cooling jacket. A temperature gradient with a surface temperature lower than the core temperature is established in the thickness direction of the solid precursor sheet, and 2-3 pressure platforms are used for stepped depressurization. S6. Cooling and Shaping: The foamed sheet is rapidly cooled to below the glass transition temperature or crystallization temperature of the thermoplastic elastomer matrix to obtain the sheet-like cushioning foam material for sports running shoes.

6. The preparation method according to claim 5, characterized in that, The acidification treatment in S1 uses a mixture of concentrated nitric acid and concentrated sulfuric acid, with a volume ratio of 1:

3. The acidification treatment is carried out by ultrasonic dispersion. The grafting reaction is carried out in anhydrous N,N-dimethylformamide, with 4,4-diphenylmethane diisocyanate as the grafting reagent. The reaction temperature is 60°C, the reaction time is 12 h, and the reaction is carried out under nitrogen protection.

7. The preparation method according to claim 6, characterized in that, The melt blending in S2 is carried out using a twin-screw extruder, and the melt blending temperature is 165-195℃.

8. The preparation method according to any one of claims 6 to 7, characterized in that, The thickness of the solid precursor sheet in S3 is 3 mm; the supercritical fluid in S4 is supercritical carbon dioxide, the impregnation temperature is 145℃, the impregnation pressure is 20 MPa, and the holding time is 2 h; the controlled pre-desorption includes reducing the pressure to 15 MPa at a depressurization rate of 0.1-1.0 MPa / min and holding it for 15 min.

9. The preparation method according to claim 8, characterized in that, The stepped pressure relief in S5 includes: a first stage reducing the pressure from 15MPa to 8MPa at a rate of 15MPa / s; a second stage holding the pressure at 8MPa for 5s; and a third stage reducing the pressure to 0.1MPa at a rate of 10MPa / s. The temperature gradient is achieved by opening the cooling jacket to establish a temperature field on the surface of the sheet that is lower than that in the core. In S6, a 20℃ cold water bath is used for quenching and cooling.